A 3D high resolution MRI method for the visualization of cardiac fibro-fatty infiltrations - K. Haliot (Nature Portfolio, 2021)
Abstract Modifications of the myocardial architecture can cause abnormal electrical activity of the heart. Fibro-fatty infiltrations have been implicated in various cardiac pathologies associated with arrhythmias and sudden cardiac death, such as arrhythmogenic right ventricular cardiomyopathy (ARVC). Here, we report the development of an MRI protocol to observe these modifications at 9.4 T. Two fixed ex vivo human hearts, one healthy and one ARVC, were imaged with an Iterative decomposition with echo asymmetry and least-square estimations (IDEAL) and a magnetization transfer (MT) 3D sequences. The resulting fat fraction and MT ratio (MTR) were analyzed and compared to histological analysis of the three regions (“ARVC triangle”) primarily involved in ARVC structural remodeling. In the ARVC heart, high fat content was observed in the “ARVC triangle” and the superimposition of the MTR and fat fraction allowed the identification of fibrotic regions in areas without the presence of fat. The healthy heart exhibited twice less fat than the ARVC heart (31.9%, 28.7% and 1.3% of fat in the same regions, respectively). Localization of fat and fibrosis were confirmed by means of histology. This non-destructive approach allows the investigation of structural remodeling in human pathologies where fibrosis and/or fatty tissue infiltrations are expected to occur.